RELATION BETWEEN THE POSTURAL POSITION AND AGUDAS CARDIOVASCULARES ANSWERS DURING THE POWER TRAINING (Fiep Bulletin - online, 2014)
The goal of this study is to check the relation between the position adopted to the realization  the exercises to the treatment for the same msucular grouping and CARDIOVASCULAR answers (blood pression, heart frequence and double product) during force treinament. Eleven healtly women, they were not using any kind of medication. 3 series of 12 maximum repetition with five minutes of interval between the series, about the REMADA CURVADA E REMANDA BAIXA SENTADA exercise .The serie.The blood pression was measuret on stillness and after the last repetition each serie. The results found did not show big different on the blood pression, blod pression and double product between two realized exercises .
Keywords: CARDIOVASCULARES answers; power training